An on-farm observational study on the prevalence and associated factors of bacteremia in preweaned dairy calves diagnosed with bronchopneumonia by thoracic ultrasonography - Antonio Boccardo; Martina Ossola; Laura Filippone Pavesi; Stefano Raineri; Alessandra Gazzola; Lorenza Sala; Chiara Francesca Magistrali; Giulia Sala; Salvatore Catania; Matteo Cornaggia; Davide Pravettoni; Antonio Marco Maisano (BMC Veterinary Research)
Abstract Background Bacteremia is a potential systemic complication of bronchopneumonia (BP) in dairy calves, which increases the risk of sepsis and mortality. However, data on bacteremia in farm conditions is still limited. This study investigates the prevalence of bacteremia in calves with BP on farms, examining isolated pathogens and the associations between thoracic ultrasonography (TUS) and non-endoscopic bronchoalveolar lavage (nBAL) findings. Results The study enclosed 13 dairy farms and included 211 eligible preweaned dairy calves, of which 88 were diagnosed with BP based on a highly sensitive threshold of ≥ 1 cm for lung consolidation detected by TUS. The affected calves underwent non-endoscopic bronchoalveolar lavage (nBAL) and blood culture procedures. Blood culture results showed a positivity rate of 6.8%, identifying Salmonella Dublin in five cases and Campylobacter fetus in one case. Twenty-four (27.2%) blood samples grew presumed bacterial contaminants, while 58 (65.9%) samples had no growth. In contrast, nBAL samples revealed a 75% positivity rate, with Pasteurella multocida and Mycoplasma bovis being the most frequently identified pathogens. No associations were observed between TUS-detected lung lesions and bacteremia. Notably, BP pathogens were not identified in blood cultures, except for one instance where Salmonella Dublin was detected in the nBAL and blood culture. Conclusions The study indicates a low prevalence of bacteremia in dairy calves with BP diagnosed through TUS, suggesting that recommending treatment or revisions in disease management related to potential bacteremia in these patients may not be warranted. The findings imply that lung lesions detected via TUS may occur independently of bacteremia, highlighting the value of TUS for early diagnosing and monitoring BP in field conditions.